Pengaruh Variasi Persentase Pakan Ampas Tahu dan Kotoran Sapi terhadap Pertumbuhan Cacing Tanah (Lumbricus rubellus) - Elza Heryensi; Aceng Ruyani; Rendy Wikrama Wardana; Bhakti Karyadi; M. Sutarno (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
This research was carried out from November to December 2023, at the Ruyani Life Sciences Learning Resources (SBIH). The aim of this research was to determine the effect of feeding tofu dregs and cow dung on the growth of earthworms (Lumbricus rubellus). The method used in this research was an experimental method, namely a Completely Randomized Design (CRD) with 6 feed treatments + 3 repetitions for continuation of undergraduate student research and 6 feed treatments + 3 repetitions for initiation. Data analysis used the Kruskall-Wallis nonparametric statistical test with Asymp. Sig. values. ≤ 0.05, and continued with the Mann-Whitney test. The research results show that the value of Asymp. Sig. parent biomass, offspring biomass, number of parent individuals, and number of Lumbricus rubellus offspring in sequence, in the 1st to 4th week of follow-up research Asymp. Sig. values. namely 0.086; 0.036; 0.140; and 0.064. In the 5th to 8th week of further research, the Asymp. Sig. value. namely 0.168; 0.047; 0.176; and 0.095. And in the 5th to 8th weeks of the research, the Asymp. Sig. value was initiated. namely 0.062; 0.010; 0.434; and 0.013. The conclusion was that feeding tofu dregs and cow dung had no real effect on parent biomass and number of parent individuals, and there was a real difference in offspring biomass and number of Lumbricus rubellus offspring in the initial study.